Dynamic tracking effect of a magnetic navigated dual hemisphere capsule robot. Issue 12 (22nd December 2022) - Zhang, Yongshun; Liu, Xu; Liu, Zhenhu; Zhao, Zihao; Dong, Hai; Wang, Dianlong
Abstract: For diagnostic and therapeutic applications in spacious spots of the gastrointestinal (GI) tract, the single rigid body capsule clinically applied is difficult to realize the fix-point posture adjustment function manipulated by the external permanent magnet system using the static balance control because the posture alignment and the locomotion interfere with each other. To realize this function easily, the dual hemisphere capsule robot (DHCR) is proposed, based on tracking effect—the axis of DHCR keeps tracking the normal orientation of the spatial universal rotating magnetic vector (SURMV). Since tracking effect employs dynamic balance control, dynamic stability of the DHCR system affects posture alignment performance. This paper focuses on posture alignment dynamic modeling and the influence of the magnetic flux density and the angular velocity of the SURMV, along with the damping coefficient of the GI tract surface on stability, obtaining the stability domains of parameters. Furthermore, to reduce error due to the uncertainties in complex GI tract environment, the sliding mode controller based on nominal model is proposed to achieve more accurate dynamic tracking, and Lyapunov theorem is employed to assess stability of controller. Finally, the tracking effect is verified through simulations and experiments, indicating that the fix-point posture adjustment can be realized with higher accuracy and efficiency.